Metal-loaded mesoporous silica and application thereof in synthesis of cyclic acid
By loading mesoporous silica with Mg, Al, and Ca as a catalyst, the problems of low conversion rate and many by-products in the preparation of cyclic acid are solved, and a high yield, high purity and low cost preparation of cyclic acid is achieved.
Patent Information
- Application Number
- CN202410821181.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-24
- Publication Date
- 2025-03-14
AI Technical Summary
The existing cyclic acid preparation technology has problems with low conversion rates and many by-products, resulting in low product yield and purity.
Mesoporous silica supported by Mg, Al, and Ca were used as catalysts to immerse metal ions into mesoporous silica by impregnation method, and cyclic acid was prepared using the catalyst in the aldol condensation reaction.
The yield and purity of the cyclic acid are significantly improved, the reaction cost is reduced, and the loading and combination of the catalyst is optimized.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of pharmaceutical and chemical engineering, in particular to a metal-loaded mesoporous silica and its application in synthesizing cyclic acids, and in particular to the preparation of a mesoporous silica simultaneously loaded with Mg, Al and Ca and its application as a catalyst in preparing cyclic acids through an aldol condensation reaction. Background Art
[0002] Cyclotonic acid is an organic compound and a major intermediate of vitamin H (biotin). It has important physiological functions in living organisms and is widely used in medicine and food. With the development of science and technology and improvements in production techniques, the research and application of cyclotonic acid has also been continuously innovated and expanded.
[0003] Cycloacids, as a major intermediate of vitamin H, have been extensively studied and understood for their physiological functions. Vitamin H is an important water-soluble vitamin that promotes the metabolism of proteins, fats, and carbohydrates, maintaining the normal function of the skin, nervous system, and digestive system. Cycloacids are one of the main metabolites of vitamin H in the body and can combine with other substances to form complex compounds that exert various physiological functions.
[0004] However, the current production of cycloacids mainly uses the traditional three-step synthesis route, which is complex and has poor product stability, resulting in low yield and purity. With the continuous deepening of research, relevant researchers have discovered that the use of new catalysts can effectively reduce the temperature of the cycloacid synthesis reaction and effectively improve the conversion rate of the synthetic preparation of cycloacids.
[0005] Impregnation is a simple and economical method for preparing supported catalysts. The carrier used in the impregnation method can provide the required physical structural properties, and the active components are mainly distributed on the surface of the carrier, ensuring its high utilization rate and low cost.
[0006] There is no report in the prior art on loading multiple metals into silica and using the silica as a catalyst to prepare cyclic acids. Summary of the Invention
[0007] In response to the problems of low conversion rate and large number of by-products in traditional cyclic acid preparation, the present invention provides a new catalyst. The catalyst is used for preparing cyclic acid by aldol condensation reaction method, which can not only reduce the reaction cost but also significantly improve the yield and purity of the product.
[0008] The present invention is achieved through the following technical solutions:
[0009] The invention provides a metal-loaded mesoporous silica, which is prepared by an excess impregnation method.
[0010] The metal is one or more of Mg, Al, Ca, Co and Cu.
[0011] The metals are derived from their nitrates, hydrochlorides or sulfates.
[0012] Furthermore, the metal is one or more of Mg, Al, and Ca.
[0013] The Mg, Al and Ca are derived from nitrates, hydrochlorides and sulfates of Mg, Al and Ca, preferably nitrates of Mg, Al and Ca.
[0014] When the magnesium nitrate, aluminum nitrate or calcium nitrate is used alone, its concentration is 10-15 g / L, 20-25 g / L, 8-10 g / L respectively; preferably 14-15 g / L, 20-22 g / L, 9-10 g / L respectively.
[0015] Furthermore, when the metal is a combination of Mg, Al, and Ca, the corresponding concentrations of magnesium nitrate, aluminum nitrate, and calcium nitrate are 3.5-6.5 g / L, 6.5-7.5 g / L, and 2.4-4.0 g / L, respectively, and preferably 4.5-5.5 g / L, 6.5-7.5 g / L, and 2.9-3.5 g / L.
[0016] The mass ratio of the aluminum nitrate, calcium nitrate and magnesium nitrate is 1:0.3-0.6:0.5-0.9; preferably: 1:0.4-0.5:0.6-0.8.
[0017] Under these conditions, the ions in the metal ion solution can be 100% impregnated into the interior of the mesoporous silica.
[0018] The silica described in the present invention is commercially available mesoporous silica particles with a specific surface area of 280 m 2 / g, pore diameter is 2-20nm, and particle size is 20-80nm.
[0019] The present invention provides a method for preparing the multi-metal loaded mesoporous silica, the method comprising the following steps:
[0020] At room temperature, the mesoporous silica is immersed in ultrapure water containing metal ions for 12-24 hours, dried, and calcined to obtain the metal-loaded mesoporous silica.
[0021] The ultrapure water for dissolving metal ions is deionized water prepared by an ultrapure water machine.
[0022] The impregnation is carried out at room temperature.
[0023] The impregnation process is carried out under shaking or stirring conditions.
[0024] The impregnation time is 12-24 hours, so that the metal is fully adsorbed into the pores of the carrier.
[0025] The drying step is drying at 80-90° C. for 24 hours.
[0026] The calcination is carried out at 550-560° C. for 3 h in an atmosphere of 5% Ar / H 2 .
[0027] The pore size of the silica is 2-20 nm.
[0028] The mass volume ratio of mesoporous silica to ultrapure water containing multiple metal ions is: 30-40:250 (g / mL)
[0029] The metal loading was 2.0-3.0%.
[0030] Furthermore, the mesoporous silica loaded with multiple metals is used as a catalyst.
[0031] Furthermore, the mesoporous silica loaded with multiple metals is used as a catalyst for aldol condensation reaction.
[0032] Furthermore, the multi-metal loaded mesoporous silica is used as a catalyst for aldol condensation reaction to synthesize cyclic acids.
[0033] The metal-loaded silica of the present invention can be used as a catalyst, particularly as a catalyst for the aldol condensation reaction to catalyze the synthesis of cyclic acids, thereby reducing reaction costs and significantly improving product yield and purity. The highest product yield and purity are achieved when the metals are a combination of Mg, Al, and Ca. DETAILED DESCRIPTION
[0034] The technical solutions of the present invention are described in further detail below with reference to specific embodiments, but the scope of protection and implementation of the present invention are not limited thereto. The present invention can be implemented in various forms and is not limited to the embodiments described herein. The embodiments are provided to provide a more thorough and comprehensive understanding of the contents disclosed herein. All technical and scientific terms used in the present invention have the same meanings as commonly understood by those skilled in the art of the present invention. The terms used herein are only for describing specific embodiments and are not to be construed in any other way.
[0035] In the following specific examples, the reaction preparation steps of the catalyst are as follows:
[0036] Example 1
[0037] (1) Weigh 1.76 g of aluminum nitrate, 0.823 g of calcium nitrate, and 1.24 g of magnesium nitrate, dissolve them in 250 ml of deionized water at 25°C, and begin shaking and stirring until evenly mixed.
[0038] (2) Weigh 30 g of mesoporous silica particles, slowly add them to the solution prepared in step (1), stir until semi-solid, and then let it stand and soak for 12 hours to obtain metal-loaded mesoporous silica.
[0039] (3) The metal-loaded mesoporous silica described in step (2) is placed in an oven at 80° C. and dried for 24 h. After the water is completely evaporated, the mixture is ground into powder using a mortar to obtain dry metal-loaded mesoporous silica.
[0040] (4) The dried metal-loaded mesoporous silica from step (3) was placed in a tube furnace and kept at 550° C. for 3 h in a 5% Ar / H 2 atmosphere. This is referred to as Cat 1.
[0041] Example 2
[0042] (1) Weigh 5.26 g of aluminum nitrate and dissolve it in 250 ml of deionized water at 25°C. Start shaking and stirring until evenly mixed.
[0043] (2) Weigh 30 g of mesoporous silica particles, slowly add them to the solution prepared in step (1), stir until semi-solid, and then let it stand and soak for 12 hours to obtain metal-loaded mesoporous silica.
[0044] (3) The metal-loaded mesoporous silica described in step (2) is placed in an oven at 80° C. and dried for 24 h. After the water is completely evaporated, the mixture is ground into powder using a mortar to obtain dry metal-loaded mesoporous silica.
[0045] (4) The dried metal-loaded mesoporous silica obtained in step (3) was placed in a tube furnace and kept at 550° C. for 3 h in an atmosphere of 5% Ar / H 2 . This is referred to as Cat 2.
[0046] Example 3
[0047] (1) Weigh 2.45g of calcium nitrate and dissolve it in 250ml of deionized water at 25℃. Start shaking and stirring until evenly mixed.
[0048] (2) Weigh 30 g of mesoporous silica particles, slowly add them to the solution prepared in step (1), stir until semi-solid, and then let it stand and soak for 12 hours to obtain metal-loaded mesoporous silica.
[0049] (3) The metal-loaded mesoporous silica described in step (2) is placed in an oven at 80° C. and dried for 24 h. After the water is completely evaporated, the mixture is ground into powder using a mortar to obtain dry metal-loaded mesoporous silica.
[0050] (4) The dried metal-loaded mesoporous silica obtained in step (3) was placed in a tube furnace and kept at 550° C. for 3 h in an atmosphere of 5% Ar / H 2 . This is referred to as Cat 3.
[0051] Example 4
[0052] (1) Weigh 3.70 g of magnesium nitrate and dissolve it in 250 ml of deionized water at 25°C. Stir the mixture until uniform.
[0053] (2) Weigh 30 g of mesoporous silica particles, slowly add them to the solution prepared in step (1), stir until semi-solid, and then let it stand and soak for 12 hours to obtain metal-loaded mesoporous silica.
[0054] (3) The metal-loaded mesoporous silica described in step (2) is placed in an oven at 80° C. and dried for 24 h. After the water is completely evaporated, the mixture is ground into powder using a mortar to obtain dry metal-loaded mesoporous silica.
[0055] (4) The dried metal-loaded mesoporous silica from step (3) was placed in a tube furnace and kept at 550° C. for 3 h in an atmosphere of 5% Ar / H 2 . This is referred to as Cat 4.
[0056] Table 1 Catalyst metal element loading in Examples 1-4
[0057] catalyst Al loading (%) Ca loading (%) Mg loading (%) Total catalyst loading (%) Cat1 0.667 0.667 0.667 2.0% Cat2 2.0 - - 2.0% Cat3 - 2.0 - 2.0% Cat4 - - 2.0 2.0%
[0058] Example 5
[0059] (1) Weigh 1.76 g of aluminum nitrate, 0.615 g of calcium nitrate, and 1.53 g of magnesium nitrate, dissolve them in 250 ml of deionized water at 25°C, and begin shaking and stirring until evenly mixed.
[0060] (2) Weigh 30 g of mesoporous silica particles, slowly add them to the solution prepared in step (1), stir until semi-solid, and then let it stand and soak for 12 hours to obtain metal-loaded mesoporous silica.
[0061] (3) The metal-loaded mesoporous silica described in step (2) is placed in an oven at 80° C. and dried for 24 h. After the water is completely evaporated, the mixture is ground into powder using a mortar to obtain dry metal-loaded mesoporous silica.
[0062] (4) The dried metal-loaded mesoporous silica obtained in step (3) was placed in a tube furnace and kept at 550° C. for 3 h in an atmosphere of 5% Ar / H 2 . This is referred to as Cat 5.
[0063] Example 6
[0064] (1) Weigh 1.76 g of aluminum nitrate, 0.737 g of calcium nitrate, and 1.35 g of magnesium nitrate, dissolve them in 250 ml of deionized water at 25°C, and begin shaking and stirring until evenly mixed.
[0065] (2) Weigh 30 g of mesoporous silica particles, slowly add them to the solution prepared in step (1), stir until semi-solid, and then let it stand and soak for 12 hours to obtain metal-loaded mesoporous silica.
[0066] (3) The metal-loaded mesoporous silica described in step (2) was placed in an oven at 80° C. and dried for 24 h. After the water was completely evaporated, the silica was ground into powder using a mortar to obtain a catalyst.
[0067] (4) The dried metal-loaded mesoporous silica obtained in step (3) was placed in a tube furnace and kept at 550° C. for 3 h in an atmosphere of 5% Ar / H 2 . This is referred to as Cat 6.
[0068] Example 7
[0069] (1) Weigh 1.76 g of aluminum nitrate, 0.86 g of calcium nitrate, and 1.16 g of magnesium nitrate, dissolve them in 250 ml of deionized water at 25°C, and begin shaking and stirring until evenly mixed.
[0070] (2) Weigh 30 g of mesoporous silica particles, slowly add them to the solution prepared in step (1), stir until semi-solid, and then let it stand and soak for 12 hours to obtain metal-loaded mesoporous silica.
[0071] (3) The metal-loaded mesoporous silica described in step (2) is placed in an oven at 80° C. and dried for 24 h. After the water is completely evaporated, the mixture is ground into powder using a mortar to obtain dry metal-loaded mesoporous silica.
[0072] (4) The dried metal-loaded mesoporous silica obtained in step (3) was placed in a tube furnace and kept at 550° C. for 3 h in an atmosphere of 5% Ar / H 2 . This is referred to as Cat 7.
[0073] Example 8
[0074] (1) Weigh 1.76 g of aluminum nitrate, 0.984 g of calcium nitrate, and 0.98 g of magnesium nitrate, dissolve them in 250 ml of deionized water at 25°C, and begin shaking and stirring until evenly mixed.
[0075] (2) Weigh 30 g of mesoporous silica particles, slowly add them to the solution prepared in step (1), stir until semi-solid, and then let it stand and soak for 12 hours to obtain metal-loaded mesoporous silica.
[0076] (3) The metal-loaded mesoporous silica described in step (2) is placed in an oven at 80° C. and dried for 24 h. After the water is completely evaporated, the mixture is ground into powder using a mortar to obtain dry metal-loaded mesoporous silica.
[0077] (4) The dried metal-loaded mesoporous silica obtained in step (3) was placed in a tube furnace and kept at 550° C. for 3 h in an atmosphere of 5% Ar / H 2 . This is referred to as Cat 8.
[0078] Table 2 Metal element loading in mesoporous silica of three metals from different concentration sources
[0079] catalyst Al loading (%) Ca loading (%) Mg loading (%) Total catalyst loading (%) Cat5 0.67 0.5 0.83 2.0% Cat6 0.67 0.6 0.73 2.0% Cat7 0.67 0.7 0.63 2.0% Cat8 0.67 0.8 0.53 2.0%
[0080] Catalyst activity evaluation
[0081] Test object: Catalysts prepared in Examples 1-8
[0082] Catalytic reaction equation;
[0083]
[0084] Synthesis steps:
[0085] Benzylamine (1), glyoxal (2), and formic acid (3) were dissolved in a reactor at a molar ratio of 1:1:1. A supported silica catalyst (2% by mass of glyoxal) was added. The mixture was stirred and heated to 90°C, where it was maintained for 3 hours to yield intermediate (4). Triphosgene was then used to ring-close intermediate (4) to yield the cyclic acid (5).
[0086] Table 3 Results of catalytic synthesis of cyclic acids by the reaction catalysts prepared in Examples 5-8
[0087] catalyst Intermediate ④ yield Intermediate ④ Purity Product ⑤ Yield Product ⑤ Purity Cat1 97.5% 99.5% 98.3% 99.4% Cat2 85.7% 94.6% 83.4% 93.2% Cat3 88.5% 96.5% 85.6% 92.3% Cat4 91.7% 98.6% 89.3% 96.8% Cat5 95.5% 97.2% 96.9% 97.1% Cat6 96.8% 98.9% 98.1% 99.1% Cat7 96.9% 98.8% 98.2% 99.3% Cat8 94.9% 96.5% 96.8% 97.2%
[0088] According to the results in Table 2, multi-component catalyst Cat 1 has the highest yield and purity. Cats 2, 3, and 4 have relatively low catalytic effects due to the relatively simple metal loadings. The catalytic effects of Cats 5, 6, 7, and 8 vary to varying degrees with the loading of Ca and Mg elements. The catalytic effect is best when the loading ratio of Al, Ca, and Mg is close to 1:1:1. The effects of catalysts Cats 1, 5, 6, 7, and 8 are significantly improved compared to single-component catalysts, but Cat 1 has the highest purity and product yield.
[0089] Example 9 Preparation of mesoporous silica adsorbed by different metal combinations
[0090] (1) Weigh 1.76 g of aluminum nitrate, 0.62 g of cobalt nitrate, and 0.59 g of copper nitrate and dissolve them in 250 ml of deionized water at 25°C. Stir and shake until evenly mixed.
[0091] (2) Weigh 30 g of mesoporous silica particles, slowly add them to the solution prepared in step (1), stir until semi-solid, and then let it stand and soak for 12 hours to obtain metal-loaded mesoporous silica.
[0092] (3) The metal-loaded mesoporous silica described in step (2) is placed in an oven at 80° C. and dried for 24 h. After the water is completely evaporated, the mixture is ground into powder using a mortar to obtain dry metal-loaded mesoporous silica.
[0093] (4) The dried metal-loaded mesoporous silica obtained in step (3) was placed in a tube furnace and kept at 550° C. for 3 h in an atmosphere of 5% Ar / H 2 . This is referred to as Cat 9.
[0094] Example 10 Preparation of mesoporous silica adsorbed by different metal combinations
[0095] (1) Weigh 0.823 g of calcium nitrate, 0.62 g of cobalt nitrate, and 0.29 g of copper nitrate and dissolve them in 250 ml of deionized water at 25°C. Stir and shake until evenly mixed.
[0096] (2) Weigh 30 g of mesoporous silica particles, slowly add them to the solution prepared in step (1), stir until semi-solid, and then let it stand and soak for 12 hours to obtain metal-loaded mesoporous silica.
[0097] (3) The metal-loaded mesoporous silica described in step (2) is placed in an oven at 80° C. and dried for 24 h. After the water is completely evaporated, the mixture is ground into powder using a mortar to obtain dry metal-loaded mesoporous silica.
[0098] (4) The dried metal-loaded mesoporous silica obtained in step (3) was placed in a tube furnace and kept at 550° C. for 3 h in an atmosphere of 5% Ar / H 2 . This is referred to as Cat 10.
[0099] Example 11 Preparation of mesoporous silica adsorbed by different metal combinations
[0100] (1) Weigh 1.24 g of magnesium nitrate, 0.62 g of cobalt nitrate, and 0.59 g of copper nitrate and dissolve them in 250 ml of deionized water at 25°C. Stir and shake until evenly mixed.
[0101] (2) Weigh 30 g of mesoporous silica particles, slowly add them to the solution prepared in step (1), stir until semi-solid, and then let it stand and soak for 12 hours to obtain metal-loaded mesoporous silica.
[0102] (3) The metal-loaded mesoporous silica described in step (2) is placed in an oven at 80° C. and dried for 24 h. After the water is completely evaporated, the mixture is ground into powder using a mortar to obtain dry metal-loaded mesoporous silica.
[0103] (4) The dried metal-loaded mesoporous silica obtained in step (3) was placed in a tube furnace and kept at 550° C. for 3 h in an atmosphere of 5% Ar / H 2 . This is referred to as Cat 11.
[0104] Table 4 Catalysts adsorbed by different metal combinations
[0105]
[0106] Table 5 Results of catalytic synthesis of cyclic acids using catalysts Cat 9-11
[0107] catalyst Intermediate ④ yield Intermediate ④ Purity Product ⑤ Yield Product ⑤ Purity Cat9 90.2% 96.3% 94.3% 96.9% Cat10 91.7% 96.4% 94.6% 97.1% Cat11 91.8% 96.7% 96.8% 97.4%
[0108] The above results show that mesoporous silica adsorbed with different metal combinations can be used as catalysts for the synthesis of cycloacids, and the catalytic activity of mesoporous silica adsorbed with different metals varies. Under the same total loading conditions, mesoporous silica adsorbed with Mg, Al, and Ca simultaneously exhibits the best catalytic activity. The optimal catalytic activity is achieved when the loading ratio of Mg, Al, and Ca is 1:1:1.
[0109] The technical features of the above embodiments may be combined in any manner. For the sake of brevity, this specification does not describe every technical feature of each embodiment. However, as long as these technical combinations do not conflict, they should be considered to be within the scope of this specification. Numerous variations and improvements may be made without departing from the scope of the present invention, and all of these fall within the scope of protection of the present invention.
Claims
1. A metal-loaded mesoporous silica, characterized in that: The metal is one or more of Mg, Al, Ca, Co and Cu, and the metal-loaded mesoporous silica is prepared by an excess impregnation method.
2. The metal-loaded mesoporous silica according to claim 1, characterized in that: The metal is derived from nitrate, hydrochloride or sulfate of Mg, Al, Ca, Co and Cu.
3. The metal-loaded mesoporous silica according to claim 1 or 2, characterized in that: The metal is one or more of Mg, Al and Ca, and the Mg, Al and Ca are derived from their nitrates, hydrochlorides or sulfates.
4. The metal-loaded mesoporous silica according to claim 3, characterized in that: When the metal is one of Mg, Al and Ca, the concentrations thereof are 10-15 g / L, 20-25 g / L and 8-10 g / L respectively; preferably 14-15 g / L, 20-22 g / L and 9-10 g / L.
5. The metal-loaded mesoporous silica according to claim 3, characterized in that: When the metal is a combination of three of Mg, Al and Ca, the concentrations of magnesium nitrate, aluminum nitrate and calcium nitrate are respectively 3.5-6.5 g / L, 6.5-7.5 g / L and 2.4-4.0 g / L, preferably 4.5-5.5 g / L, 6.5-7.5 g / L and 2.9-3.5 g / L.
6. The metal-loaded mesoporous silica according to claim 5, characterized in that: The mass ratio of the aluminum nitrate, calcium nitrate and magnesium nitrate is 1:0.3-0.6:0.5-0.9; preferably: 1:0.4-0.5:0.6-0.
8.
7. The method for preparing the metal-loaded mesoporous silica according to any one of claims 1 to 6, characterized in that: At room temperature, mesoporous silica is immersed in ultrapure water containing metal ions for 12-24 hours, dried, and calcined to obtain the metal-loaded mesoporous silica; the mass volume ratio of mesoporous silica to ultrapure water containing multiple metal ions is: 30-40:250 g / mL.
8. Use of the metal-loaded mesoporous silica according to any one of claims 1 to 6 in the preparation of a catalyst.
9. Use of the metal-loaded mesoporous silica according to any one of claims 1 to 6 in preparing a catalyst for aldol condensation reaction.
10. Use of the metal-loaded mesoporous silica according to any one of claims 1 to 6 as a catalyst for aldol condensation reaction in the synthesis of cyclic acids.